Ktunaxa and the Shape of Religious Freedom - Moon, Richard (2019)
The most frequently made criticism of the Supreme Court of Canada’s decision in Ktuxana v. BC echoes a familiar and more general criticism of the Anglo-American understanding of religious freedom. The Court’s narrow or ‘protestant’ conception of religious freedom, which is focused on the individual – on his/her belief or commitment and his/her personal relationship with a transcendent God – is said to have the effect of denying meaningful protection to Indigenous and other spiritual systems that emphasize ritual and community life, and that recognize a spiritual presence in the natural world. I will argue that in a religiously/culturally diverse society such as Canada, the protection granted by s. 2(a) (the Charter’s religious freedom right) must be limited to those practices that can be viewed, at least substantially, as personal to the individual or internal to the religious group. The failure of the courts to give religious freedom protection to important Indigenous practices may stem not from a narrow conception of religion but rather from a recognition of the limits of religious freedom in a democratic political community. However, I will argue that the majority of the Court in Ktunaxa went further than this and introduced a limit on the scope of religious freedom that unnecessarily and artificially limits the freedom’s protection based on a Christian understanding of religion, as concerned centrally with the worship of a divine power. In earlier cases, the Court has limited the protection of s.2(a) by defining the concept of religion narrowly or interpreting the practices of a particular religion narrowly so that they did not include communal connections and practices.
Keywords: Richard Moon